Studying The Effect of Zircon Dioxide on The Corrosion Resistance of Porcelain Enamel - Hassan, Nagham Salman (Nahrain University College of Engineering Journal, 2011)
Among various coating systems for industrial and engineering applications, glass ceramic coatings have advantages of chemical inertness, high temperature stability and superior mechanical properties such as abrasion, impact etc as compared to other coating materials. Besides imparting required functional properties such as heat, abrasion and corrosion resistance to suit particular end use requirements, the glass ceramic coatings in general also provide goodadherence, defect free surface and refractoriness. This research tends to produce a cheep and effective glass- ceramic coating from glass culletand different percent of crystallization agents ZrO2, and study the final corrosion resistance properties of them. After several set of acid resistance testing at temperatures range (25, 50, 75,100,125 oC) it has been found that porcelain enamel with (4 wt %) ZrO2 has the best acid corrosion resistance